Relative Contribution of Nitrogen Absorption, Remobilization, and Partitioning to the Ear During Grain Filling in Chinese Winter Wheat - Zhou, Bangwei; Serret, Maria Dolores; Pie, Jordi Bort; Shah, Syed Sadaqat; Li, Zhijian (Frontiers in Plant Science, 2018)
Knowledge of the function of the ear as a key organ in the uptake, remobilization and partitioning of nitrogen is essential for understanding its contribution to grain filling and thus guiding future breeding strategies. In this work, four Chinese winter wheat genotypes were grown on a 15N-enriched nutrient solution. N absorption and further remobilization to the flag leaf, the ear and the mature grains were calculated via the 15N atom % excess. The results indicated that the high yields of the Chinese wheat genotype were determined by higher grain numbers per ear, with greater plant height and a larger ear size, while the thousand-grain weight did not affect grain yield. In the mature grains, 66.7% of total N was remobilized from the pre-anthesis accumulation in the biomass, while the remaining 33.3% was derived from the N taken up during post-anthesis. From anthesis to two weeks after the anthesis stage, the flag leaf remobilized 3.67 mg of N outwards and the ear remobilized 3.87 mg of N inwards from the pre-anthesis accumulation in each plant. The positive correlation between ear Nrem and grain Nrem indicated that the ear was an important organ for providing N to the grain, whereas the remobilized N stream from the leaves was not correlated with grain Nrem, thus indicating that flag leaf N was not translocated directly to the grain. The grain Nrem was negatively correlated with the ear N concentration throughout grain filling, which suggested that higher-yielding genotypes had better sink activity in the ear, while Rubisco played a critical role in N deposition. Therefore, to improve yield potential in wheat, the N accumulation in the ear and the subsequent remobilization of that stored N to the grains should be considered. N accumulation and remobilization in the ear may at least be valuable for Chinese breeding programs that aim at optimizing the sink/source balance to improve grain filling.